Implementasi Metode Weighted Moving Average dan Least Square Untuk Persediaan Obat Pada Apotek Kimia Farma - Anggreini Anggreini; Samsudin Samsudin (LKP Unity Academy, 2026)
Drug inventory management is an important aspect of pharmacy services because it directly affects medicine availability for patients. Inaccurate inventory planning may lead to stock shortages (stockout) or excess inventory (overstock), which can reduce service quality and increase storage costs. This study aims to develop a drug inventory forecasting system for Kimia Farma Pharmacy using the Weighted Moving Average (WMA) and Least Square methods. The research employed the Research and Development (R&D) approach, while the system was developed using the Rapid Application Development (RAD) method. The dataset consisted of historical sales records of ten types of medicines from January to November 2023, collected through observation, interviews, and literature review. The results indicate that the developed system is capable of automatically forecasting future drug inventory based on historical sales data. The Weighted Moving Average method provides forecasts that are more responsive to recent demand changes by assigning greater weights to the latest observations, while the Least Square method generates forecasts based on sales trends. The developed system assists pharmacy staff in determining appropriate inventory levels, thereby reducing the risk of stock shortages and overstock situations. Therefore, the proposed forecasting system can improve the effectiveness of drug inventory management at Kimia Farma Pharmacy.